We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
250
1
avatar+86 

The quadratic \(x^2-6x+66\) can be written in the form \((x+b)^2+c\), where \(b\) and \(c\) are constants. What is \(b+c\)?

 Oct 16, 2018

Best Answer 

 #1
avatar+5776 
+2

\(x^2 - 6x + 66 = \\ x^2 - 6x + 9 - 9 + 66 = \\ (x-3)^2 + 57 \\ b=-3,~c=57\)

.
 Oct 16, 2018
 #1
avatar+5776 
+2
Best Answer

\(x^2 - 6x + 66 = \\ x^2 - 6x + 9 - 9 + 66 = \\ (x-3)^2 + 57 \\ b=-3,~c=57\)

Rom Oct 16, 2018

13 Online Users